Estudio para el diseño del cuarto de telecomunicaciones del departamento de redes de la Universidad Nacional de Loja. - Neira Peña, Eduardo Alejandro (2015)
Today, increasing demand for Internet, growth in data volume and the incidence of Information Technology, have made the Fourth Telecommunications expand your productivity, optimize the services it provides and this increased availability. Therefore, several companies have chosen to increase their storage capacity and improve availability. The redesign of the Room of Telecommunications of the Universidad Nacional de Loja, tries to decrease the problem about the processes of interchanging of information and communication between the members of the university community both internally and externally which needs a technological restructuring to organize, Safeguard and manage internal processes of the university. By this reason in the first chapter it is carried out a study of the rules that are used to design the Room of Telecommunication such as ANSI / TIA / EIA-942 which specifies parameters for the design of these telecommunications infrastructures ANSI / TIA -606, which specifies the management for telecommunications cabling system and ANSI / TIA-607 that provides guidelines for grounding system. In the second chapter, an actual pattern is presented which is in the Room of Telecommunications, parameters such as physical and logical topology, servers list having with their specifications, active equipment and its main characteristics, all of these backgrounds will allow us an analysis of the current situation of the infrastructure in order to stablish solutions in the redesign. In the third chapter there is the design proposal of the Room of Telecommunications of the Departamento de Redes de la Universidad Nacional de Loja, complying with each of the specified parameters in ANSI / TIA / EIA-942 like the architectural part, telecommunications aspects, security and mechanics. The fourth chapter presents a reference budget about the price of the implementation of the project which is $ 535,893.28 American dollars, this investment includes the prices of the passive and active devices, access control, video monitoring system, fire system, air conditioning system, lighting system and civil works. Finally It is possible to demonstrate that with applying of a Room of Telecommunications it will be possible to have a system of Telecommunications which guarantee to obtain information to improve the processes and therefore it will help to decrease the time and the resources as well as the improvement the services of the staff working in the net of Universidad Nacional de Loja.